Analisis Efektivitas Penerapan Program Kebijakan Pemutihan Pajak Kendaraan Bermotor dalam Upaya Meningkatkan Pendapatan Pajak Daerah di SAMSAT Kabupaten Tegal - Patria, Yoka Mai (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
One such policy is to increase the number of taxpayers who own motor vehicles but have not been paying taxes. To address this issue, local governments offer an option to waive administrative sanctions for motor vehicle taxes. The purpose of this research is to analyze the effectiveness of the implementation of the motor vehicle tax amnesty policy, as well as to identify obstacles and efforts to overcome these obstacles in the program’s execution. This study adopts a qualitative approach with descriptive analysis methods with secondary data as its basis. The research results indicate that the effectiveness of the motor vehicle tax amnesty policy is relatively successful, evident in the increased achievement of motor vehicle tax revenue targets at the Tegal District SAMSAT in the years 2021- 2022. Despite the increase in revenue, there was a decline in realization in 2022 compared to 2021. However, the Tegal District SAMSAT has made efforts to enhance the collection of motor vehicle tax revenue.